A brief history of logarithmic strain measures in nonlinear elasticity. Issue 1 (17th December 2018) - Martin, Robert J.; Münch, Ingo; Eidel, Bernhard; Neff, Patrizio
Abstract: We demonstrate that the notion of logarithmic strain tensors in nonlinear elasticity theory, which is commonly attributed to Heinrich Hencky, is actually due to the geologist G. F. Becker, who was the first to consider a fully three‐dimensional logarithmic stress response in an 1893 article.